The economic implications of voting requirements for the establishment of the European Monetary Union - Raimund Krumm; Bernhard Herz (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1996)
The European Council selects the EMU participants by a vote with a qualified majority. These voting requirements influence the benefit-cost-considerations of the EU states and may make it necessary to loosen the convergence criteria and/or to grant side payments, in order to achieve the necessary number of votes. However, not even making use of these options can guarantee the realization of a monetary union in every case. For this reason, supporting economic and institutional measures, such as convergence programs and the so-called stability pact, which diminish the binding character of the voting requirements, are of great importance.
Keywords: D71; F33; F36; F42; H87; 330; European Monetary Union; voting requirements; convergence; stability concessions; side payments; Eurozone; Abstimmungsregel; Neue politische Ökonomie; EU-Staaten